Design and Tensile Performance of Face-to-Face Flange Connections of Cold-Formed Steel C-Section - S. N. A. Ismail; I. R. Muhammad Alif; A. F. Kamarudin (Journal of Structural Monitoring and Built Environment, 2025)
Cold-formed steel (CFS) is widely used in structural applications due to its high strength-to-weight ratio and material efficiency. However, the performance of its connections is often governed by localized resistance mechanisms. This study investigates the behaviour of face-to-face flange (FTFF) sleeve connections in CFS C-sections, with particular emphasis on bearing and shear resistances. Analytical design resistances were determined in accordance with Eurocode 3 (EC3), and experimental validation was conducted through laboratory testing of 9 specimens with varying plate thicknesses (0.75 mm and 1.00 mm), sleeve lap lengths of 200 mm, and screw quantities (4 and 6). Tensile test of the several types of connection styles was performed using a 120-ton universal testing machine. From the experimental results, it shows increases in material thickness and screw quantity primarily enhance connection performance through improved bearing resistance and load transfer efficiency. The ultimate tensile load (Pu) ranged from 15.20 kN to 29.21 kN.  The calculated normalization ratios, defined as the ratio of the experimental load Pu to the design bearing resistance, exceeded unity and ranged from 1.27 to 1.67. This confirms that bearing deformation governed the failure mechanism. In contrast, the shear resistance ratios remained below unity, within a relatively narrow range of 0.54 to 0.85, indicating a significant margin, which is also influenced by variations in thickness and screw configurations. The failure modes were dominated by bearing deformation with hole elongation and localized plate yielding, accompanied by minor screw tilting, with no screw fracture observed. Finally, optimal FTFF connection performance can be achieved through a balanced design that enhances bearing and shear resistances by appropriately configuring material thickness and fastener number to improve connection capacity.